Seasonal influence on tomato fruit metabolome profile Implications for ABA signaling in multi-stress resilience - Pardo-Hernández, Miriam (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 The Authors. Published by Elsevier Masson SAS.. All rights reserved.